The response of the water cycle to landscape configuration and composition in two Chilean basins - Marieta Hernández-Sosa; Mauricio Aguayo; Jorge Hurtado; Ovidio Llompart (Environmental and Sustainability Indicators)
Land use/cover change (LUCC) and landscape patterns have an important influence on the hydrological cycle. However, it is still unknown how hydrological processes and streamflow respond to changes in landscape configuration and composition in hydrological basins. The relationship between landscape metrics and hydrological variables in two Chilean basins was analyzed for the last 4 decades. Aggregation, shape and diversity metrics were obtained using Fragstats software, and hydrological components were simulated by the TETIS hydrological model. Pearson correlation coefficients (PCC) and partial least squares (PLSR) analysis were used to determine how landscape patterns influence hydrological processes and streamflow behavior. The most significant negative correlations occur in the wet season between aggregation and shape metrics on crop soils and evapotranspiration, infiltration, and baseflow regime behavior. The PLSR analysis shows that the second component-related landscape metrics of young plantations explain the highest percentage of variation in hydrological components. The results of this research improve our understanding of the effects of landscape configuration and composition on the hydrological cycle and can be used for land planning and water resource management within the basins.